The Agricultural Exit Problem: An Empirical Assessment - Bezemer, Dirk (Washington, DC: World Bank, 2012)
This paper documents the development of agricultures share in total employment in the developing world, and relates it to developments in per capita income. As suggested by Engel's Law, it finds a strong and robust negative correlation between GDP per capita and the share of the labor force employed in agriculture. Based on this result, the rates of exit from agriculture by 2015 for different regions of the world plus China and India are projected. The results show that Asian countries have or soon will reach a tipping point in their agricultural transformation when the absolute size of the agricultural workforce will begin to decline and large numbers of agricultural workers can be expected to leave agriculture by 2015. If Asia is to significantly reduce its levels of rural-urban income inequality, then the exit from agriculture will need to be even larger. The situation in Africa is more sanguine. If African countries continue to grow slowly if at all, then their agricultural work forces will continue to increase to 2015, even though agricultures employment share will fall slightly. The analysis shows little change in LAC, MENA or EE&CA.